Evaluation of Policies on Aceh Qanun Regulation - Said Mayzar Mulia; Ismail (Britain International for Academic Research (BIAR) Publisher, 2020)
In Aceh development activities are basically carried out actively, arief and wise including in applying a regional policy in the form of Circular (SE) Number 450/21770 which contains about the prohibition of holding recitation other than I'tiqad Ahlussunnah Waljamaah which is sourced from the Shafi'ite School law well, around last December 2019 that made a commotion in the public in Aceh. This causes great concern for the community regarding the clash of the Circular with article 14 paragraph (3) of the Aceh Qanun Number 8 of 2014 which regulates the Principles of Islamic Sharia stating that the holding of worship which does not refer not to the Syafi'i sect is permitted. Given as long as within the framework of the Hanafi, Maliki and Hambali mazhas by always promoting harmony, ukhuwah Islamiah and peace within the Muslim community, even though hierarchically the Circular Letter (SE) legislation is lower than Qanun, which is likely to use political means as a driving force for local government.